Analisis Komentar Hasil Belajar Siswa Menggunakan Opinion Summarization - Suardani, Putri; Divayana, Yoga; Saputra, Komang Oka (Majalah Ilmiah Teknologi Elektro; Vol 18 No 1 (2019): (Januari - April) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i01.P09, 2019)
The quality of a teacher has become the center of attention in research in the field of education. The quality of the teacher is not only measured by the qualifications and insights of a teacher, but also dedication and commitment in the classroom One of the things that can be used to assess the quality of teachers is to assess the opinions of students. Therefore, student opinions at the end of the class such as questionnaires are needed to help teachers understand student learning behavior and improve the quality of teaching in the classroom. Opinion summarization is a method to make summaries automatically from a set of opinions about a particular target. Opinion summarization will explore the features of one's opinion, capture whether the opinion includes positive or negative opinions, then summarize the results. Based on the results of testing and analysis that has been done in the previous discussion, it can be concluded that the accuracy value obtained is 93,44% with 97,66% precision and 92,85%. recall. This proves that the system that has been built is accurate and can help the company to see the performance of the teachers.